The Role of Azerbaijan’s selective bandwagoning with Russia in its relative neutrality during the 44-day war - Khalilov, Altun (ADA University, 2024)
Starting with the early 2000s, Russia emerged as the major regional power over almost all of the post-Soviet space. As such, for decades Russia was viewed as the preserver of the status quo when it came to the conflict in and around Karabakh. It is widely accepted as a fact that no tangible change can occur on the ground toward the resolution of the Armenian-Azerbaijani conflict without Russia's approval, especially through military means. Yet, when the 44-day war broke out between Armenia and Azerbaijan in 2020, Russia chose not to directly intervene in the war, knowing that with its military superiority over Armenia, Azerbaijan would come out as the winning side in the war. The aim of this study is to discuss the foreign policy approach of Azerbaijan towards Russia during the last decade and how it contributed to Russia's relative neutrality in the 44-day war.
Keywords: Foreign policy -- Azerbaijan -- 21st century; Russia (Federation) -- Foreign relations -- Azerbaijan; Karabakh Conflict (2020) -- Foreign relations; Azerbaijan -- Foreign relations; Public and International Affairs